Comparative assessment of the diagnostic efficacy of [18F]AlF-NOTA-FAPI-04 and [18F]FDG PET/CT imaging for detecting postoperative recurrence in gastric cancer patients: a pilot study - Yang, Jian; Wu, Yong; Zhang, Yanyin; Peng, Xiang; Jiang, Chengzhi; Zhou, Wanjing; Dai, Jiashun; Xie, Aimin; Ye, Hui; Zheng, Kai (Frontiers in Oncology, 2024)
PurposeThis study aimed to compare the efficacy of [18F]AlF-NOTA-FAPI-04 PET/CT with that of [18F]FDG PET/CT for detecting postoperative recurrence in patients with gastric cancer.MethodsThis single-center retrospective clinical study was performed at Hunan Cancer Hospital between December 2020 and June 2022. The participants underwent both [18F]AlF-NOTA-FAPI-04 and [18F]FDG within 14 days. Histopathologic examination, morphological imaging, and/or follow-up imaging were used as a reference for the final diagnosis. We recorded the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of [18F]AlF-NOTA-FAPI-04 and [18F]FDG PET/CT for detecting local recurrence, lymph node metastasis and distant metastasis. The SUVmax and background ratio (TBR) of local recurrence and metastases between [18F]FDG and [18F]AlF-NOTA-FAPI-04 PET/CT were compared using paired-sample t tests.ResultsForty-seven patients (27 males, aged 25–68 years) with gastric cancer after curative resection (27 with adenocarcinoma, 17 with signet ring cell carcinoma and 4 with mucinous adenocarcinoma) were included in the study. [18F]AlF-NOTA-FAPI-04 accumulation was significantly greater than that of [18F]FDG in terms of local recurrence (SUVmax, 11.65 vs 3.48, p< 0.0001; TBR, 12.93 vs 2.94, p< 0.0001), lymph node metastasis (SUVmax, 13.45 vs 3.05, p=0.003875; TBR, 12.43 vs 2.21, p=0.001661), and distant metastasis (SUVmax, 11.89 vs 2.96, p < 0.0001; TBR, 13.32 vs 2.32, p< 0.0001). Despite no statistical comparison was made with [18F]FDG, [18F]AlF-NOTA-FAPI-04 imaging exhibited high levels of sensitivity, specificity, PPV, NPV, and accuracy for detecting postoperative local recurrence, lymph node metastasis, and distant metastasis in patients with gastric cancer.Conclusion[18F]AlF-NOTA-FAPI-04 has demonstrated potential for more accurate tumor re-evaluation in GC, thus enhancing treatment decision-making.